The racial politics of division : interethnic struggles for legitimacy in multicultural Miami - Gosin, Monika (Cornell University Press, 2019)
"Focusing on interminority tensions between African Americans, white Cubans, and Afro-Cubans in Miami when national trends toward majority-minority spaces had just begun to emerge, The Racial Politics of Division exposes the roots of interethnic conflict and their connection to the race-making practices of the Anglo elite, adding dimension to modern debates about race, blackness, immigration, and interethnic relations in multicultural America"-- Provided by publisher.
Keywords: Miami (Fla.) -- Ethnic relations.; Miami (Fla.) -- Race relations.; Minorities -- Florida -- Miami -- Social conditions.; Ethnic conflict -- Florida -- Miami.; Minorités -- Floride -- Miami -- Conditions sociales.; Conflits ethniques -- Floride -- Miami.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Ethnic conflict; Ethnic relations; Minorities -- Social conditions; Race relations; Florida -- Miami